Implementation of Problem-Based Learning Based on Local Wisdom to Improve Students' Critical Thinking Skills - Beni Setiawan; Fiainil Mufidah; Ruqoyyah Amilia Andania; Raka Prasetyo Nurhaddi (Jurnal Pemberdayaan Masyarakat, 2025)
Critical thinking is one of the essential skills students need to navigate the challenges of the 21st century. Critical thinking can be developed through effective learning models and local wisdom approaches that support learning. This research aims to describe the improvement of critical thinking skills and students' responses to a Problem-Based Learning model based on local wisdom. The research used a quasi-experimental design. The subjects targeted are seventh-grade students at a state junior high school in Kediri Regency. The data collection techniques used are Pre-test and Post-test with essay questions containing critical thinking indicators, and the students' responses after the learning process. The research results showed a significant improvement in critical thinking skills in the classroom, using the Problem-Based Learning model based on local wisdom. The students' responses to this model were categorized as good. This study concludes that the implementation of the Problem-Based Learning model, grounded in local wisdom, is effective in enhancing students' critical thinking skills. The contributions of this research were expected to develop an innovative learning model incorporating local wisdom in science education, aiming to achieve the goal of developing critical thinking skills.